TV 3326 for Alzheimer's dementia: a novel multimodal ChE and MAO inhibitors to mitigate Alzheimer's-like neuropathology. (9th March 2020) - Uddin, Md Sahab; Kabir, Md Tanvir; Rahman, Md Motiar; Mathew, Bijo; Shah, Muhammad Ajmal; Ashraf, Ghulam Md
Abstract: Objectives: Alzheimer's disease (AD) is one of the most prevalent neurodegenerative disorders and a well-recognized cause of dementia with ageing. In this review, we have represented the ChE and MAO inhibitory potential of TV 3326 against AD based on current scientific evidence. Key findings: The aetiology of AD is quite complex and not completely understood. However, it has been observed that AD involves the deposition of abnormal amyloid beta (Aβ), along with hyperphosphorylation of tau, oxidative stress, low acetylcholine (ACh) level and biometal dyshomeostasis. Due to the complex nature of AD aetiology, active research is required in the areas of development of multitarget drugs with 2 or more complementary biological functions, as they might represent significant progress in the AD treatment. Interestingly, it has been found that TV 3326 (i.e. ladostigil) is regarded as a novel therapeutic agent since it has the potential to cause inhibition of monoamine oxidase (MAO) A and B, and acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) in the brain. Furthermore, it has the capacity to reverse memory impairments, which further suggests the ability of this drug to elevate cholinergic activity in the brain. Summary: TV 3326 can avert oxidative–nitrative stress and gliosis. It has also been confirmed that TV 3326 contains neuroprotective and anti-apoptotic properties. Therefore, this distinctive combined inhibition of ChE and MAO along with its neuroprotective property makes TV 3326 a useful drug in the treatment of AD.